Uma nova abordagem para o estudo do planejamento e controle da produção (PCP): a ótica da Teoria da Complexidade - Dutra, Fernando Augusto Ferreira; Erdmann, Rolf Hermann (Revista Gestão da Produção Operações e Sistemas, 2006)
Nowadays, one of the main organizational challenges is to adapt to an environment that changesfaster than the organizations can follow. Such organizations are still attached to the mechanistic model. Thiswork originated from the idea that the organizational systems no more behave in a linear way. It is suggestedhere a new approach, under the view of the Complexity Theory, in order to study and analyze the ProductionPlanning and Control (PPC) system of the organizations. The Complexity Theory suggests that the systemsshould be observed as Complex Adaptive Systems (CAS). These types of systems have as a basic property theability to adjust their behavior in order to deal with new situations in their environment. It is believed that theobservation of the PPC as a CAS can contribute for the organizations in a way that they can obtain significantinsights in order to manage their operations.Keywords: Operation Management; PPC; Complexity Theory.